Comparison of the Effectiveness of Acceptance and Commitment Therapy (ACT) and Behavioral Activation Therapy (BAT) on Quality of Life and Self-Care Behaviors in Patients with Type 2 Diabetes - Ahmadi, Reza; Leilabadi, Lida; Salehi, Mahdieh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Behavioral Activation Therapy (BAT) on quality of life and self-care behaviors in patients with type 2 diabetes. Methods and Materials: The research employed a quasi-experimental design with pre-test, post-test, and three-month follow-up, using a three-group format (ACT, BAT, and control). A total of 60 patients with type 2 diabetes from Tehran health centers were selected through convenience sampling and randomly assigned to one of the three groups, with 20 participants in each. Both intervention groups received eight two-hour sessions administered face-to-face by the researcher. The ACT protocol was based on Hayes' model, emphasizing psychological flexibility, mindfulness, and value-driven behavior, while the BAT protocol followed Levenson’s structure focused on re-engagement with rewarding activities. Data were collected using the Quality of Life Questionnaire (SF-36) and the Diabetes Self-Care Behavior Questionnaire. Descriptive statistics and mixed ANOVA, along with Bonferroni post-hoc tests, were used for data analysis via SPSS. Findings: Results indicated that both ACT and BAT significantly improved quality of life and self-care behaviors compared to the control group (p < .001). However, ACT was significantly more effective than BAT in enhancing both outcome variables at post-test and follow-up. Within-subject analyses showed significant changes over time for both interventions, and between-subject effects confirmed group-based differences. Post-hoc tests revealed sustained improvements in the ACT group, while BAT showed moderate but less stable effects. Conclusion: Both ACT and BAT are effective psychological interventions for improving self-care and quality of life in type 2 diabetic patients, with ACT demonstrating stronger and more lasting outcomes.